A comparative study of the economic efficiency of ritual-based Sorghum bicolor farming in Indonesia - WILLYBRORDUS LANAMANA; IMACULATA FATIMA; PHILIPUS NERIUS SUPARDI (Asian Journal of Agriculture, 2026)
Abstract. Lanamana W, Fatima I, Supardi PN. 2026. A comparative study of the economic efficiency of ritual-based Sorghum bicolor farming in Indonesia. Asian J Agric 10 (1): g100149. https://doi.org/10.13057/asianjagric/g100149. Sorghum bicolor is an alternative food source in the Ende District, East Nusa Tenggara, Indonesia, given its low productivity and inefficient yields. Farming rituals have been proven to increase S. bicolor productivity. Therefore, this study aims to analyze the economic efficiency level of farmers who engage in S. bicolor farming ritual practices, and who do not, as well as to review the factors affecting both practices. The Cobb-Douglas Stochastic Frontier production function analysis was adopted. Production variables included land, seeds, fertilizers, labor, and pesticides. This study was conducted in four S. bicolor potential sub-districts, using a census method with 385 farmers as respondents. The farmers from three sub-districts who practiced farming rituals included Wolojita (50 farmers), Lepembusu Kelisoke (75 farmers), and Kotabaru (50 farmers). A total of 210 farmers from the Nangapenda Sub-district did not practice farming rituals. The results showed that farming rituals were more effective, with technical, allocative, and economic efficiencies of 91%, 95%, and 92%, respectively. However, without farming rituals, 78%, 78%, and 64% were achieved in technical, allocative, and economic efficiencies, respectively. A benefit-cost ratio analysis of >1 showed that S. bicolor farming was feasible. Factors that positively affected economic efficiency comprised education, farmer group membership, and rituals. Local governments need to ensure agricultural extension schedules support traditional calendars to facilitate simultaneous planting. The transformation of farmer groups into agricultural input providers was also required.